The New H.N.I.C. : the Death of Civil Rights and the Reign of Hip Hop. - Boyd, Todd (NYU Press, 2003)
When Lauryn Hill stepped forward to accept her fifth Grammy Award in 1999, she paused as she collected the last trophy, and seeming somewhat startled said, "This is crazy, 'cause this is hip hop music.'" Hill's astonishment at receiving mainstream acclaim for music once deemed insignificant testifies to the explosion of this truly revolutionary art form. Hip hop music and the culture that surrounds it--film, fashion, sports, and a whole way of being--has become the defining ethos for a generation. Its influence has spread from the state's capital to the nation's capital, from the Pineapple to th.